HR ANALYTICS MODELLING - Mitha Veronica (Politeknik Bisnis Indonesia, 2023)
HR Analytics Modeling namely, a data driven approach in human resource management that uses analytical tools to collect, analyze, and interpret human resource data to improve decision-making within the organization to optimize strategic decisions related to human resources such as recruiting, training and development, compensation and performance management. Data collection begins with collecting data related to employees and human resources, including data on employee profiles, compensation, performance, absenteeism, job satisfaction, and so on. The collected data is then analyzed using various data analysis techniques to gain useful insights and information. In this stage, the data is processed and linked to other data such as historical information, normal or average data.